Characterization of Barium Hexaferrite and Iron Sand as Microwave Absorbing Materials - Naibaho, Yeni P.S; Humaidi, Syahrul; Rianna, Martha; Diana, Linda (Universitas Pendidikan Mandalika, 2024)
This research aims to analyze the characteristics of Barium Hexaferite and iron sand as microwave absorbing materials, their influence on microwave absorption properties, and the frequency range of waves produced by these materials. The research method used is the Co-Precipitation method. Dissolve barium hexapherite and iron sand in distilled water with the appropriate mass ratio. The results of this study show that the synthesis of iron sand and barium hexapherite material produces a single phase material. The single phase material is shown through X-ray diffraction pattern data, namely iron sand and barium hexapherite, namely hematite and barium hexapherite. Iron sand and barium hexapherite materials are characterized using EDS which shows a composition that is close to stoichiometry. Observations using VNA show that iron sand and barium hexapherite materials are able to absorb electromagnetic waves at a radar wave frequency of 11.1 GHz, which is -25.64 dB.